ANALISIS PENERAPAN SISTEM INFORMASI SPMI BERBASIS DIGITAL DALAM MENINGKATKAN EFEKTIVITAS AUDIT MUTU INTERNAL DI UNIVERSITAS MULAWARMAN - Fitriadi, Ahmad; Wan, Markus; Batang, Samson; Andy Abeh, Yohanes; Wibawa, Radhitya; Mebang, Desi Natalia; Azainil, Azainil; Haeruddin, Haeruddin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Digital transformation in the Internal Quality Assurance System (IQAS) at higher education institutions has become a strategic step to enhance the effectiveness of internal quality audits (IQA). This research aims to analyze the implementation of a digital-based IQAS information system at Mulawarman University and assess its impact on the effectiveness of internal quality audit implementation. A descriptive qualitative approach was used in the form of a case study, with data collection techniques including interviews, documentation, and observation. The results show that the developed cloud-based spreadsheet information system has improved timeliness, transparency, efficiency, and participation of work units in the IQA process. The digitalized audit process facilitates collaboration between auditors and auditees, supports document tracking, and speeds up decision-making. Although the system is not yet fully automated, this implementation has reinforced a data-driven quality culture and sustainability. The main recommendation from this study is the development of an integrated web application system, enhanced user training, and further studies to evaluate the long-term impact on institutional quality. These findings contribute theoretically to the literature on the digitization of education quality and offer practical benefits for strengthening quality management policies in higher education institutions.